Clinical Activity and Safety of Penpulimab (Anti-PD-1) With Anlotinib as First-Line Therapy for Unresectable Hepatocellular Carcinoma: An Open-Label, Multicenter, Phase Ib/II Trial (AK105-203) - Han, Chun; Ye, Sisi; Hu, Chunhong; Shen, Liangfang; Qin, Qun; Bai, Yuxian; Yang, Shizhong; Bai, Chunmei; Zang, Aimin; Jiao, Shunchang; Bai, Li (Frontiers in Oncology, 2021)
Abstract Objective: This study aims to assess the efficacy and safety of penpulimab (a humanized anti–PD-1 IgG1 antibody) with anlotinib in the first-line treatment of Chinese patients with uHCC. Methods: In this open-label multicenter phase Ib/II trial, patients with histologically or cytologically confirmed uHCC, without previous systemic treatment, aged 18-75 years old, classified as BCLC stage B (not amenable for locoregional therapy) or C, with Child–Pugh score ≤7 and ECOG performance status ≤ 1 were enrolled. Patients received penpulimab (200 mg intravenous [i.v.] Q3W) and oral anlotinib (8 mg/day, 2 weeks on/1 week off). The primary endpoint was objective response rate (ORR). Secondary endpoints included safety, disease control rate (DCR), progression-free survival (PFS), time to progression (TTP), duration of response (DoR) and overall survival (OS). This trial is registered with ClinicalTrials.gov (NCT04172571). Results: At the data cutoff (December 30, 2020), 31 eligible patients had been enrolled and treated with a median follow-up of 14.7 months (range, 1.4-22.1). The ORR was 31.0% (95% CI, 15.3%-50.8%), and the DCR was 82.8% (95% CI, 64.2%-94.2%). The median PFS and TTP for 31 patients were 8.8 months (95% CI, 4.0-12.3) and 8.8 months (95% CI, 4.0-12.9) respectively. The median OS was not reached; the 12-month OS rate was 69.0% (95% CI, 48.9%-82.5%). Only 19.4% (6/31) of patients had grade 3/4 treatment-related adverse events (TRAEs). Conclusion: Penpulimab plus anlotinib showed promising antitumor activity and a favorable safety profile as first-line treatment of patients with uHCC.